Neuropsychiatric Profiles and Oral Rehabilitation in Patients Undergoing Plastic Surgical Correction of Maxillofacial Defects - Hassan Masood, Ghulam Shabir Shaikh, Sadia Rasheed, Khan Muhammad Taha, Shanzay Azhar Qureshi, Saher Sultan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Maxillofacial defects, whether congenital, traumatic, or acquired, cause significant physical, functional, and psychological impairment. These deformities often lead to difficulties in mastication, speech, and facial expression, accompanied by profound emotional distress and social withdrawal. Although reconstructive plastic surgery can restore anatomy and function, its neuropsychiatric impact and correlation with oral rehabilitation outcomes remain underexplored. Objective: To evaluate the neuropsychiatric profiles, functional recovery, and oral rehabilitation outcomes in patients undergoing plastic surgical correction for maxillofacial defects. Methods: This prospective observational study was conducted in the Department of Surgery, Punjab Dental Hospital, Lahore, Pakistan, from January 2023 to June 2023, enrolling 100 patients aged 18–65 years with maxillofacial defects of traumatic, congenital, or post-oncologic origin. Neuropsychiatric evaluation included the Beck Depression Inventory (BDI), Hamilton Anxiety Rating Scale (HAM-A), and Mini-Mental State Examination (MMSE) administered preoperatively and 6 months postoperatively. Oral rehabilitation outcomes were assessed through the Prosthetic Adaptation Scale (PAS), Masticatory Efficiency, and Esthetic Satisfaction (VAS) scores. Data were analyzed using SPSS v25.0, applying paired t-tests and Pearson correlation, with p < 0.05 considered statistically significant. Results: The mean age of patients was 37.4 ± 10.2 years, with males constituting 62%. Preoperatively, 58% showed moderate-to-severe depression and 55% had significant anxiety. Postoperative evaluation at 6 months showed marked improvement: mean BDI decreased from 22.6 ± 7.9 to 11.4 ± 5.6 (p < 0.001) and HAM-A from 18.3 ± 6.7 to 9.8 ± 4.1 (p = 0.002). Masticatory efficiency improved from 57 ± 10% to 79 ± 8% (p = 0.001), and esthetic satisfaction (VAS) increased from 4.1 ± 1.2 to 8.3 ± 1.1 (p < 0.001). A strong inverse correlation was found between depressive symptoms and prosthetic adaptation (r = –0.65). Conclusion: Plastic surgical correction of maxillofacial defects significantly enhances both psychological well-being and oral functional outcomes. Early psychological assessment, structured prosthodontic rehabilitation, and multidisciplinary postoperative care are essential to achieve optimal physical and emotional recovery in affected patients. Keywords: Maxillofacial defects, plastic surgery, oral rehabilitation, neuropsychiatric profile, depression, anxiety, prosthetic adaptation, Pakistan.